2018
DOI: 10.1007/s10120-018-0809-y
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized trial comparing efficacy and safety of paclitaxel/capecitabine and cisplatin/capecitabine in advanced gastric cancer

Abstract: BackgroundWe compared efficacy and safety of paclitaxel/capecitabine therapy followed by capecitabine for maintenance (PACX) versus cisplatin/capecitabine therapy (XP) in advanced gastric cancer.MethodsMulticenter, randomized, phase III trial was conducted in China (December 2009–February 2014). Adults (n = 320) with histologically confirmed, untreated metastatic/unresectable gastric or gastroesophageal junction adenocarcinoma; with ≥ 1 measureable lesions according to Response Evaluation Criteria in Solid Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 21 publications
(28 reference statements)
1
35
0
Order By: Relevance
“…Combination of paclitaxel and capecitabine showed a mPFS of 5.0 months in first-line treatment in advanced gastric patients. 12 In the Chinese patient population analysis, the mPFS of capecitabine/cisplatin and 5-fluorouracil/cisplatin were 7.2 and 4.5 months, respectively. 13 In another phase III study, docetaxel and cisplatin plus fluorouracil were compared with cisplatin and fluorouracil, and the median time to progression was 5.6 and 3.7 months, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Combination of paclitaxel and capecitabine showed a mPFS of 5.0 months in first-line treatment in advanced gastric patients. 12 In the Chinese patient population analysis, the mPFS of capecitabine/cisplatin and 5-fluorouracil/cisplatin were 7.2 and 4.5 months, respectively. 13 In another phase III study, docetaxel and cisplatin plus fluorouracil were compared with cisplatin and fluorouracil, and the median time to progression was 5.6 and 3.7 months, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Chemotherapy resistance, whether primary or acquired, is common ( 6 ). The differences in molecular expression between tumors have resulted in different responses of patients with cancer to chemotherapeutic drugs ( 4 5 ). The accurate selection of chemotherapeutic drugs, which maximize the effectiveness of chemotherapy and reduce the toxic and side effects, is one of the most critical issues in the clinical application of chemotherapy ( 4 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capecitabine is an oral preparation of antimetabolites that act specifically on tumor cells. After oral administration, capecitabine is rapidly absorbed through the intestinal mucosa and converted into 5-Fu through a three-step enzyme chain reaction in vivo (4). Capecitabine blocks the intracellular thymidine synthase from deoxyribonucleotide uridine and interferes with DNA synthesis (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present retrospective study, the addition of docetaxel or paclitaxel to the conventional combination of platinum and fluoropyrimidines in adjuvant chemotherapy for patients after curative gastrectomy did not demonstrate any benefit either in DFS or in overall survival. The addition of docetaxel or paclitaxel in chemotherapy regimens was shown to be effective in advanced gastric cancer [9][10][11]. For resectable gastric cancer, the results of the SAMIT study showed that sequential paclitaxel followed by fluoropyrimidines did not improve DFS compared to tegafur and uracil (UFT) or S-1 monotherapy [5].…”
Section: Discussionmentioning
confidence: 99%